2012
DOI: 10.1148/radiol.12112565
|View full text |Cite
|
Sign up to set email alerts
|

Advanced Solid Tumors Treated with Cediranib: Comparison of Dynamic Contrast-enhanced MR Imaging and CT as Markers of Vascular Activity

Abstract: DCE MR imaging and DCE CT can depict vascular response to antiangiogenic agents with response evident at day 7. Improved reproducibility with MR imaging favors its use in trials with small patient numbers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
34
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(35 citation statements)
references
References 36 publications
0
34
1
Order By: Relevance
“…Advances in hardware and software that have enhanced the signal-tonoise ratio and improvements in contrast resolution with gadolinium-based contrast agents (GBCAs) 1 make contrast-enhanced MR imaging (CE-MRI) a comparable or better diagnostic tool than computed tomography and other conventional imaging methods. [2][3][4][5] Further advances in dynamic CE-MRI perfusion 6 and contrast-enhanced magnetic resonance angiography (MRA) 7 have improved the e‹ciency of clinical diagnoses, and highlight the importance of imaging techniques in diagnostic medicine.…”
Section: Introductionmentioning
confidence: 99%
“…Advances in hardware and software that have enhanced the signal-tonoise ratio and improvements in contrast resolution with gadolinium-based contrast agents (GBCAs) 1 make contrast-enhanced MR imaging (CE-MRI) a comparable or better diagnostic tool than computed tomography and other conventional imaging methods. [2][3][4][5] Further advances in dynamic CE-MRI perfusion 6 and contrast-enhanced magnetic resonance angiography (MRA) 7 have improved the e‹ciency of clinical diagnoses, and highlight the importance of imaging techniques in diagnostic medicine.…”
Section: Introductionmentioning
confidence: 99%
“…Koh et al 81 found ADC measurements from DW-MRI to be highly reproducible, with a coefficient of repeatability of 13.3%. Messiou et al 82 also reported the intrapatient coefficients of variation (CVs) for all DCE-derived parameters to be within the range of 8-30%, except for V p . 82 The most reproducible DCE-derived parameters were the enhancing fraction (CV 5 8.6%), followed by K trans (CV 5 13.9%) and initial area under the time-concentration curve over 60 seconds (CV 5 15.5%).…”
Section: Challenges With Integration Of Functional Mri Into Clinical mentioning
confidence: 91%
“…Messiou et al 82 also reported the intrapatient coefficients of variation (CVs) for all DCE-derived parameters to be within the range of 8-30%, except for V p . 82 The most reproducible DCE-derived parameters were the enhancing fraction (CV 5 8.6%), followed by K trans (CV 5 13.9%) and initial area under the time-concentration curve over 60 seconds (CV 5 15.5%). The stability of these parameters in HNC need to be established further prior to clinical implementation.…”
Section: Challenges With Integration Of Functional Mri Into Clinical mentioning
confidence: 91%
“…(Cao) Compartment modeling can extract quantitative perfusion metrics that are being investigated to predict radiation-induced normal tissue damage, assess combined chemo-radiotherapy effects and efficacy as well as optimization of the timed application of anti-vascular agents. (Axel 1980;Miles 1991) Despite the promise of conventional DCE-CT to serve as an imaging biomarker (Kim, Kamaya et al 2014;Mains, Donskov et al 2014), reproducible findings have not easily been achieved and the correlation between DCE-CT and other measures of tissue vascularity and fibrosis have been difficult (Huda, Scalzetti et al 2000;Roberts, Roberts et al 2001;Miles 2003;Messiou, Orton et al 2012). The reasons for these challenges are complex but can typically be categorized as (a) limitations and uncertainties in the measurement and raw data acquisition, (b) assumptions related to implementation of the transport methodology, and, of course, (c) the strength of the relatively simple kinetic models in realistically describing the underlying microscopic transport behavior.…”
Section: Dynamic Contrast-enhanced Ctmentioning
confidence: 99%